Principles and practice of sport management - Masteralexis, Lisa Pike; Barr, Carol A.; Hums, Mary A. (Jones & Bartlett Learning, 2012)
From the basic knowledge and skill sets of a sport manager to current trends and issues in the sport management industry, Principles and practice of sport management, Fourth Edition provides the foundation for students as they study and prepare for a variety of sport management careers. The editors and chapter contributors, all well-known sport industry professionals, show students how to apply their new knowledge and skills to any segment of the sport industry, from high school to the international arena. The Fourth Edition has undergone substantial content updates, including discussion of new developments and manag3rial approaches happening in the sport world, and new chapters on club management and new media in sport. This best-selling text provides a comprehensive, current overview of the sport management field and introduces students to various segments of the industry, supplying them with the knowledge they need to successfully pursue a career in sports. New To The Fourth Edition. -Discussion of professionalism in electronic correspondence (text, e-mail). -The impact of social networking on sport management. -Social responsibility in sport management. -Advances in television technology (HDTV, 3D TV) and how they have influenced the sport industry. -Agents, gambling, and amateurism. -Online sponsorshipsubanner ads, pop-ups, and company links. -Sport and new media. -Discussion on how sporting goods and licensed products impact sports organizations. -Additional case studies including Is the NFL Conduct Policy Working?; The Outsourcing of College Ticket Sales Operations; and Introducing... The FedEx, I mean, the Discover Orange Bowl! --Book Jacket.